Peranan Efektivitas Pengelolaan Sarana Prasarana Pada Sekolah Rendah Islam Integrasi Al-Qudwah Selangor Malaysia - Najiyullah Subhani Lubis; Isra Hayati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Infrastructure is a crucial element in supporting the effectiveness of the educational process in schools. This study analyzes the management of infrastructure facilities at Sekolah Rendah Islam Integrasi Al-Qudwah Selangor, Malaysia, focusing on effectiveness, constraints, solutions, and strategies for improvement. The objectives of this research are to evaluate the role of effective infrastructure management, identify the constraints encountered, propose solutions for enhancing management, and analyze the school's strategies for improving the quality of infrastructure facilities. This research employs a qualitative approach with descriptive analysis, gathering data through interviews, observations, document reviews, and literature studies. The findings indicate that while the management of infrastructure facilities significantly supports the educational process, there are challenges such as inadequate facilities and irregular evaluations. Proposed solutions include the procurement of better-structured facilities and the implementation of regular evaluations. Strategies for improvement encompass long-term planning, collaboration among schools, and systematic maintenance. This study aims to provide insights into the development of infrastructure facilities in other schools with similar characteristics.